Energy transformations and dissipation of nonlinear internal waves over New Jersey's continental shelf - E. L. Shroyer (Nonlinear Processes in Geophysics, 2010)
The energetics of large amplitude, high-frequency nonlinear internal waves (NLIWs) observed over the New Jersey continental shelf are summarized from ship and mooring data acquired in August 2006. NLIW energy was typically on the order of 105 Jm−1, and the wave dissipative loss was near 50 W m−1. However, wave energies (dissipations) were ~10 (~2) times greater than these values during a particular week-long period. In general, the leading waves in a packet grew in energy across the outer shelf, reached peak values near 40 km inshore of the shelf break, and then lost energy to turbulent mixing. Wave growth was attributed to the bore-like nature of the internal tide, as wave groups that exhibited larger long-term (lasting for a few hours) displacements of the pycnocline offshore typically had greater energy inshore. For ship-observed NLIWs, the average dissipative loss over the region of decay scaled with the peak energy in waves; extending this scaling to mooring data produces estimates of NLIW dissipative loss consistent with those made using the flux divergence of wave energy. The decay time scale of the NLIWs was approximately 12 h corresponding to a length scale of 35 km (O(100) wavelengths). Imposed on these larger scale energetic trends, were short, rapid exchanges associated with wave interactions and shoaling on a localized topographic rise. Both of these events resulted in the onset of shear instabilities and large energy loss to turbulent mixing.